One-year results of a balloon expandable endoprosthesis as a bridging stent for branched endovascular aortic repair - Usai, Marco Virgilio; Gargiulo, Mauro; Haulon, Stéphan; Tielliu, Ignace; Böckler, Dittmar; Verhagen, Hence; Fernández, Alba Méndez; Austermann, Martin Josef (Journal of vascular surgery, 2023)
Objective - This post-market multicenter registry aimed to evaluate the safety and performance of the GORE VIABAHN VBX balloon expandable endoprosthesis (VBX stent) implanted in peripheral vessels. In this subgroup analysis, we assessed the outcomes of the VBX stent as a bridging stent graft for visceral vessels during branched endovascular aortic repair at 1 year. - Methods - A single cohort from a prospective, multicenter, observational, 16-site European registry. Patients were enrolled from November 2018 to March 2022. Endpoints included 1-year primary patency (PP), primary assisted patency (PAP), and secondary patency (SP), stent graft-related death and serious adverse events through 30 days. - Results - Seventy-three patients were enrolled in this registry sub-cohort, 57 (78.1%) were male, and the mean age was 73 ± 8.1 years. Thoracoabdominal aneurysms predominated the cohort with 68 patients (93.2%), followed by five patients (6.8%) with pararenal and infrarenal aneurysms. Overall, 233 target vessels were treated with the index bridging graft. The overall per stent graft analysis demonstrated a PP of 95.8% at 1 year; PAP was 95.8%, and SP reached 97.9%. The per-target vessel analysis demonstrated a PP, PAP, and SP in the celiac trunk of 100%, 100%, and 100%; in the superior mesenteric artery of 96.0%, 96.0%, and 100%, and in the renal arteries of 94.2%, 94.2%, and 95.1%, respectively. Four patients (5%) died at 1 year; none of the deaths were device-related. The composite endpoint of target vessel technical success and freedom from VBX stent-related serious adverse events through 30 days was achieved in 98.6% of patients. - Conclusions - In this prospective post-market multicenter registry, the VBX stent demonstrated excellent results at 1 year, with almost 96% primary patency and 98% secondary patency. Patency in the renal arteries seems to be lower. Nevertheless, the VBX stent appears to be a reliable bridging stent for branched endovascular aortic repair.
Gesehen am 19.08.2024